2005
DOI: 10.1074/jbc.m413327200
|View full text |Cite
|
Sign up to set email alerts
|

CNK1 Is a Scaffold Protein That Regulates Src-mediated Raf-1 Activation

Abstract: Raf-1 is a regulator of cellular proliferation, differentiation, and apoptosis. Activation of the Raf-1 kinase activity is tightly regulated and involves targeting to the membrane by Ras and phosphorylation by various kinases, including the tyrosine kinase Src. Here we demonstrate that the connector enhancer of Ksr1, CNK1, mediates Src-dependent tyrosine phosphorylation and activation of Raf-1. CNK1 binds preactivated Raf-1 and activated Src and forms a trimeric complex. CNK1 regulates the activation of Raf-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 55 publications
3
56
0
Order By: Relevance
“…The following antibodies were used: anti-NF-κB1 p105/p50, anti-NF-κB2 p100/p52, anti-RelA, anti-RelB, anti-pS176/180(177/ 181) IKKα(β), anti-IKKα, anti-IKKβ, anti-pS32 IκBα, and anti-IκBα (Cell Signaling Technology); anti-pY204 ERK1/ 2, anti-ERK2, and anti-α-tubulin (Santa Cruz Biotechnology). Anti-CNK1 antibody was described elsewhere (11).…”
Section: Reagentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The following antibodies were used: anti-NF-κB1 p105/p50, anti-NF-κB2 p100/p52, anti-RelA, anti-RelB, anti-pS176/180(177/ 181) IKKα(β), anti-IKKα, anti-IKKβ, anti-pS32 IκBα, and anti-IκBα (Cell Signaling Technology); anti-pY204 ERK1/ 2, anti-ERK2, and anti-α-tubulin (Santa Cruz Biotechnology). Anti-CNK1 antibody was described elsewhere (11).…”
Section: Reagentsmentioning
confidence: 99%
“…Retroviral pMSCV vectors expressing shRNAs against CNK1 [shCNK1; 5′-GTAGTACTGCTAGTCATGG-3′; targeting the 3′ untranslated region (UTR)] or firefly luciferase (shGL2; 5′-CGTACGCGGAATACTTCGA-3′) and viral transduction were described previously (11). Transduced MDA-MB-231 and MCF10A cells were selected with 1 μg/mL puromycin to obtain stable polyclonal cell lines.…”
Section: Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such proteins might also protect the Nregion against phosphatases and could provide an explanation for the constitutive S446 phosphorylation of B-Raf that is observed in different cell types and species. Indeed, recent findings have shown that the adapter protein CNK1 binds to Raf-1 in an inducible and Ras-GTP-dependent manner, whereas its association with B-Raf and pre-activated Raf-1 mutants with increased N-region charge is constitutive and Ras-GTP independent (Ziogas et al, 2005). Thus, proteins like CNK1 may assist in the stabilization of the primed state.…”
Section: Regulation Of B-raf Signallingmentioning
confidence: 99%